Przyczyny i skutki inwazji czeremchy amerykańskiej Prunus serotina w ekosystemach leśnych - Halarewicz, Aleksandra (Leśne Prace Badawcze, 2011)
Alien plant invasions result from a complex interaction between the traits of introduced species and the properties of recipient ecosystems. The traits of Prunus serotina together with its undemanding habitat requirements have allowed it to spread easily over continental Europe. In particular, P. serotina is capable of acclimating to a wide range of light environments while maintaining a positive carbon balance and growth rate. It also produces chemical compounds with allelopathic activity. Furthermore, P. serotina has a high reproductive capacity through both sexual and vegetative reproduction, and its fruits and seeds are effectively dispersed by birds and mammals. The paper reviews the multi-stage changes in species composition, structure and dynamics of recipient communities, in forest phytocenoses vulnerable to neophyte invasion.